Relationships of the expertise level of taekwondo athletes with electromyographic, kinematic and ground reaction force performance indicators during the dollyo chagui kick - Sarmet Moreira, Pedro Vieira [UNESP]; Franchini, Emerson; Fernandes Ervilha, Ulysses; Goethel, Márcio Fagundes [UNESP]; Cardozo, Adalgiso Coscrato [UNESP]; Gonçalves, Mauro [UNESP] (My University, 2018)
Background and Study Aim: Taekwondo is an Olympic combat sport in which the outcome of the match is determined by points scored by kicking. By the competition rules, the roundhouse kick directed to the head (dollyo chagui) concedes the tripling of points, compared to that directed to the chest height. The aim of the study is knowledge about kinematic and neuromuscular indicators of the dollyo chagui (DC) executed by elite and subelite taekwondo athletes. Material and Methods: Seven elite (23.6 ±2.1 years old; 69 ±9.5 kg; 168 ±5 cm) and 7 sub elite (22.4 ±1.3 years old; 66.8 ±14.2 kg; 174 ±11 cm) black belt taekwondo athletes were evaluated on the DC kick performance. Biomechanical measures included angular and linear velocities of leg and pelvis, ground reaction force, premotor time, reaction time, kicking time and cocontraction index (CI) of EMG activation of 8 leg muscles (vastus lateralis, biceps femoris, rectus femoris, tensor fasciae latae, adductor magnum, gluteus maximus, gluteus medium and gastrocnemius lateralis), obtained through the analysis of DC kicks. Results: Timing indicator and CI were lower (p<0.05) in an elite group, while linear peak velocities (toe, ankle and knee), angular velocities (knee and hip), and ground reaction force (GRF) were higher (p<0.05) in the elite than in the sub-elite group. The reaction time, co-contraction and speed of kicks are discriminant factors concerning competitive level. Conclusions: The specific neuromuscular and technical differences between groups found in this study indicate that to improve the performance of sub-elite athletes these indicators could be useful in monitoring their training status. Furthermore, starting to contract specific muscles early and to perform the kicking phase with the gluteus maximum more relaxed is associated with a more efficient high kick performance. If a coach uses this information to design specific training methods, there could be a potential to improve the kick performance of the athletes.
Keywords: Biomechanics; Co-contraction; Reaction time; Velocity